Technology anxiety in consumer purchase behaviour / Dr. Syahida Abd Aziz and Dr. Roziyana Jafri - Abd Aziz, Syahida; Jafri, Roziyana (Universiti Teknologi MARA, Kedah, 2022)
Rapidly evolving advanced technologies in various fields are constantly influencing consumer purchase behaviour. Specifically, the past decade has demonstrated technology hugely reshaping consumer expectations of relevant products and personal preferences (Rangaswamy et al., 2022). Despite the embedment of advanced technologies in a product to enhance product utility, consumers are increasingly anxious and concerned with the extraordinary pervasiveness of technology applications, hence elevating their demurrals of employing available technological systems. As such, the appraisal of consumer sentiments, including anxiety levels, towards the installed technology systems in products is consequential to thoroughly understanding consumer purchase intention.